DATA ENVELOPMENT ANALYSIS AS A TOOL FOR ENERGY EFFICIENCY MEASUREMENT; AN APPLICATION TO THE CROP PRODUCTION SECTOR OF INDIA - Aditi Garg , Dr. Smita Verma , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Efficient use of energy is the need of the present generation which is already facing an energy shortage and a boom in population which will surpass China as the most populous country in the world by 2023. Any measure for improvement can only be developed when we can get the analysis of the efficiency measures of the energy consuming sectors. Agriculture is one of the top three energy consuming sectors in India. In this paper we provide a measure of energy efficiency of crop production sector of 20 states of India for 2015-20 considering two major energy inputs fertilizers and electricity and single output crop production, using the Data envelopment analysis Variable returns to scale input-oriented model. The results of our study show that 5 states out of 20 are found to be energy efficient throughout the period 2015-20.